Advances in accounting education. Vol. 10 - Schwartz, Bill N.; Catanach, Anthony H. (Advances in accounting education,, 2009)
Advances in Accounting Education is a referenced, academic research annual whose purpose is to help meet the needs of faculty members interested in ways to improve their classroom instruction. We publish thoughtful, well-developed articles that are readable, relevant and reliable. Articles may be either empirical or non-empirical. They emphasize pedagogy i.e. explaining how faculty members can improve their teaching methods or how accounting units can improve their curricula/programs.